Five difficulties in writing the truth: different types of problems in translating Heine’s poetry into Spanish - Balzer Haus, Berit (Estudios de Traducción, 2011)
Every translator of Heinrich Heine’s poetry and prose has been confronted with the difficulty, not to say impossibility, of translating into the target language certain words which in their majority are compound nouns. The present papers studies a series of samples taken from the different typologies of Heine’s neologisms and other rhetoric devices which are found scattered about his texts with a truly malicious delight. Every one of these translation difficulties shall be classified according to the implications it necessarily evokes in a German reader, due to his linguistic and cultural background. After formulating a taxonomy of difficulties, we shall propose several possible strategies a future translator can adopt: 1) infratranslation, 2) hypertranslation, 3) paraphrasing, 4) omission, 5) compensation through comments and explaining notes, 6) compensation for loss of semantic, connotative or pragmatic- discursive force, or 7) transcoding for a functional equivalence.